Pengaruh EPS, BOPO, ROA Terhadap Harga Saham Sektor Perbankan - Ardha Dewa Bagaskara; Erna Puspita; Sigit Puji Winarko (Yayasan Literasi Ilmiah Indonesia, 2026)
Purpose: This research is designed to investigate how Earning Per Share (EPS), Operating Expenses to Operating Income (BOPO), and Return on Assets (ROA) dictate equity values across banking firms between 2023 and 2025.. Method: Employing a quantitative approach, this investigation utilizes multiple linear regression to evaluate the data. The target population encompasses publicly traded banks registered on the Indonesia Stock Exchange (IDX) throughout the 2023–2025 timeframe. Under a purposive sampling technique with specific predetermined requirements, a final dataset of 99 observations was successfully established for further evaluation.. Finding: The empirical evidence demonstrates that both Earning Per Share (EPS) and Operating Expenses to Operating Income (BOPO) exert a notable impact on equity pricing. Consequently, maximizing EPS while maintaining efficient BOPO levels tends to stimulate higher market prices. On the contrary, Return on Assets (ROA) exhibits no meaningful influence over share prices, indicating that asset-based profitability yields minimal consideration during investment appraisals within this framework.. Novelty: The distinctiveness of this inquiry centers on exploring the banking sector amidst the 2024 equity market fluctuations, leveraging a newly extended dataset running through 2025. This approach offers fresh insights into evolving investor sentiment and shifting market pricing dynamics within Indonesia's financial landscape.